24 weeks of Pilates-aerobic and educative training to improve body fat mass in elderly Serbian women - Rutjes AWS (Dove Medical Press, 2014)
Anne WS Rutjes,1 Marcello Di Nisio2,31Institute of Social and Preventive Medicine, University of Bern, Bern, Switzerland; 2Department of Medical, Oral, and Biotechnological Sciences, University G D'Annunzio of Chieti-Pescara, Chieti, Italy; 3Department of Vascular Medicine, Academic Medical Center, Amsterdam, the NetherlandsWe read with interest the article by Ruiz-Montero et al, in which the authors used a before-and-after study design to examine changes in body composition (fat mass and lean body mass) related to an aerobic-Pilates program in elderly Serbian women.1 The authors concluded that "a combined program of aerobic and Pilates, carried out under the supervision of an instructor, at least twice a week, produces health benefits in functionally independent women over the age of 60". This conclusion is overly optimistic and not supported by the evidence provided. View original paper by Ruiz-Montero and colleagues.